Utilização de alumínio recoberto por aspersão térmica em tubulação de condensadores evaporativos - Baroni, Luis Felipe Sverzut (2013)
In evaporative condenser production, galvanized steel has become the most suitable material for piping system production, since it has high corrosion resistance and relative low commercial value. With proper surface treatment, it is possible to make aluminum an efficient alternative for the replacement of galvanized steel on these refrigeration equipment. In this work, thermal spray and organic coating spray were used to cover an aluminum substrate in order to achieve a material condition with better corrosion resistance and better thermal properties. Electrochemical impedance spectroscopy (EIS) and open circuit potential were used to evaluate different surface coatings performance. Microstructural characterization of the coatings was made through scanning electron microscope (SEM) and confocal microscope. Electrochemical tests showed that a coating composed of an inner layer of NiCr and external layer of AA1100 aluminum alloy applied by thermal spraying is not effective for the protection of aluminum tubes exposed to an alkaline environment with pH above 10.5, as in evaporative condensers piping system. Yet the coating comprised of a AA1100 aluminum alloy applied by thermal spraying and subsequent application of epoxy resin is a viable alternative for this application.